Lines resistant to downy mildew in the sunflower genetic collection at VIR - V. A. Gavrilova; T. G. Stupnikova; L. G. Makarova; N. V. Alpatieva; Yu. I. Karabitsina; E. B. Kuznetsova; I. A. Anisimova (Труды по прикладной ботанике, генетике и селекции)
Background. Downy mildew (DM) caused by the fungus Plasmopara halstedii (Farl) Berl. & De Toni) is one of the most harmful diseases of sunflower (Helianthus annuus L.). Due to the pathogen’s attacks, annual seed harvest losses range between 30% and 70%. Lines resistant to new races of the pathogen should be obtained for the development of commercial sunflower hybrids.Materials and methods. Downy mildew resistance of 323 lines and 10 cultivars from the sunflower collection was assessed in the field at the Kuban Experiment Station of VIR in 2017–2018. Line VIR 845, susceptible during all years of observations, was used as a control. Resistance genes were identified by means of the molecular analysis using diagnostic markers of the Plarg, Pl6 and Pl8 genes that confer resistance to many known P. halstedii races.Results. The founder varieties of VIR’s lines were susceptible to a varying extent. Thirty-nine lines were resistant in 2016 and 2018; among those, 36 lines were susceptible in 2017. Presumably, a more virulent P. halstedii race became widespread in 2017, compared to the races that prevailed in 2016 and 2018, so the genes that determined resistance in 2016 and 2018 turned out to be ineffective. Lines ТА 716-18, VIR 768, and VIR 800, having originated from interspecific hybrids, exhibited absence of pathogenic damage during 3 years of the trials. Molecular markers of the Plarg, Pl6 and Pl8 genes were detected in most lines that demonstrated resistance in 2016 and 2018. There were no markers in lines VIR 768 and VIR 800, whereas in ТА 716-18 the markers of Plarg and Pl8 were present.Conclusion. As a result of the long-term studies, a trait-specific genetic collection was established for sunflower. It comprises genotyped lines with various effective DM resistance genes. Lines ТА 716-18, VIR 768 and VIR 800 appeared highly resistant to the pathogen and probably possess new resistance genes/alleles introgressed from wild species.